Pro-inflammatory Cytokines Drive Deregulation of Potassium Channel Expression in Primary Synovial Fibroblasts - Haidar, Omar; O’Neill, Nathanael; Staunton, Caroline A.; Bavan, Selvan; O’Brien, Fiona; Zouggari, Sarah; Sharif, Umar; Mobasheri, Ali; Kumagai, Kosuke; Barrett-Jolley, Richard (Frontiers in Physiology, 2020)
The synovium secretes synovial fluid, but is also richly innervated with nociceptors and acts as a gateway between avascular joint tissues and the circulatory system. Resident fibroblast-like synoviocytes’ (FLS) calcium-activated potassium channels (KCa) change in activity in arthritis models and this correlates with FLS activation. Objective To investigate this activation in an in vitro model of inflammatory arthritis; 72 h treatment with cytokines TNFα and IL1β. Methods FLS cells were isolated from rat synovial membranes. We analyzed global changes in FLS mRNA by RNA-sequencing, then focused on FLS ion channel genes and the corresponding FLS electrophysiological phenotype and finally modeling data with ingenuity pathway analysis (IPA) and MATLAB. Results IPA showed significant activation of inflammatory, osteoarthritic and calcium signaling canonical pathways by cytokines, and we identified ∼200 channel gene transcripts. The large KCa (BK) channel consists of the pore forming Kcnma1 together with β-subunits. Following cytokine treatment, a significant increase in Kcnma1 RNA abundance was detected by qPCR and changes in several ion channels were detected by RNA-sequencing, including a loss of BK channel β-subunit expression Kcnmb1/2 and an increase in Kcnmb3. In electrophysiological experiments, there was a decrease in over-all current density at 20 mV without change in chord conductance at this potential. Conclusion TNFα and IL1β treatment of FLS in vitro recapitulated several common features of inflammatory arthritis at the transcriptomic level, including increase in Kcnma1 and Kcnmb3 gene expression.